Uso de filmes eletrofiados de PVA contendo dendrímeros PAMAM para liberação transdérmica de Ibuprofeno - Silva, Leandro Couto da (2021)
Electrospinning has been consolidated as a technique for obtaining polymeric membranes, due to its versatility associated with the wide applicability of the most diverse polymers. In this technique, polymeric associations can be used, called blends, in order to achieve a certain applicability, which would not be achieved if only one polymer was used, thus polymer blends have distinct characteristics that can improve the properties of the materials obtained. Through this technique it was possible to produce membranes of PVA, PVA with dendrimer and PVA with dendrimer and ibuprofen in order to evaluate the effects on drug release. The membranes were composed of 8% PVA in relation to the 10 mL solution prepared, 6,4% drug in relation to the polymer mass and 10% dendrimer also in relation to the PVA mass. The membranes produced as well as the precursor materials were characterized, in order to verify the actual incorporation of all agents, through Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), Xray Diffraction (DRX) and Fourier Transform Infrared Spectroscopy (FTIR). The results obtained with such analyzes demonstrated efficiency in the electrospinning process, since there was confirmation of the presence of precursor materials, PVA, dendrimer and Ibuprofen, in the production of membranes. Through the release assays it was possible to determine the drug content released in the PVA membrane, about 66.12% in a period of 270 min. The PVA membrane with dendrimer had a release content of 100% in the same period, and within 15 min of release 98.82% of the drug was released. The release profile was applied to some kinetic models, and the most suitable for both membranes, PVA with Ibuprofen and PVA with dendrimer and Ibuprofen, was the Weibull model, taking into account the R2ajust criteria and the Akaike criterion (AIC). Therefore, the material obtained showed good potential to be used as a vehicle for transdermal delivery, being suitable for in vivo studies.